Brain Morphological Changes in Acute Combined Intoxication with Asaleptin and Ethyl Alcohol - A. M. Golubev; D. V. Sundukov; A. R. Bashirova; M. A. Golubev (Общая реаниматология)
Objective: to study brain morphological changes in acute combined intoxication with asaleptin and ethyl alcohol. Material and methods. The cerebral cortex (the parietal region) was histologically examined in 26 patients (19 men and 7 women, 22 to 63 years old) who had died of acute (first 24hour) combined intoxication with asaleptin and ethyl alcohol. Blood ethyl alcohol concentrations varied from 1.4 to 4.1%o. Brain pieces were fixed in 10% formalin and embedded in paraffin. Histologic specimens were stained with hematoxilin and eosin by Nissl and analyzed using the Olympus BX 41 microscope. Morphological changes in the nerve cells were assessed according to existing classification and protocols («Histopathology of the central nervous system», Meditsina Publishers, Moscow, 1969). Results. In cases of death from acute combined intoxication with asaleptin and ethyl alcohol morphological patterns of acute brain neuronal damages were detected. They included (a) nonspecific reversible and irreversible neuronal damages and (b) circulatory disorders comprising of vascular plethora in the microcircula-tory bed and developed perivascular and pericellulary edema. Conclusion. Detection of brain neuronal damage patterns in acute combined intoxications with asaleptin and ethyl alcohol might aid in justification of an immediate death cause as a supplement to forensic chemical analysis. Key words: brain morphological changes, intoxications, asaleptin, ethyl alcohol.